Toward Ethical Labor Practices in the Ready-Made-Garment Industry: A thematic document analysis of inadequate working conditions in Bangladesh - Segerlind,Jessica (2025)
This thesis is conducted through a thematic document analysis and explores the reasons why inadequate labor conditions in Bangladesh have remained unchanged since the tragedy of the Rana Plaza collapse in 2013. The findings identify two significant factors that constrain the work toward fair working conditions in the ready-made-garment industry: 1) an ongoing ‘glocal’ conflict among stakeholders in the industry, and 2) vulnerabilities of export-dependency among involved actors in Bangladesh. Based on new institutionalist approaches and the assumption of a Liberal International Order, it further investigates possible solutions in terms of voluntary corporate commitments, particularly for voluntary sustainability standards, to function as the internationally leading strategy for advanced labor conditions in the ready-made-garment industry in low and lower-middle-income countries. The assessment indicates a possibility for voluntary sustainability standards in this field, given its global recognition and credibility. To reach its full potential, however, several issues, considering the representation deficit and symbolic intentions of brands, need to be managed by those organizations first.
Keywords: Bangladesh; corporate social sustainability; garment industry; institutionalism; International Labour Organization; ILO; labor conditions; Liberal International Order